Butyriboletus hainanensis (Boletaceae, Boletales), a new species from tropical China - Liang, Zhi-Qun; An, Dong-Yu; Jiang, Shuai; Su, Ming-Shen; Zeng, Nian-Kai (Phytotaxa, 2016)
Butyriboletus hainanensis (Boletaceae, Boletales) is described as a new species from Hainan Province, a tropical region of China. It is morphologically characterized by a large, brown pileus with thick context and thin hymenophore, a blue-red-black color change of hymenophore and context, a yellow to brownish red stipe with faint reticulations, and an interwoven trichodermal pileipellis. Phylogenetic analyses of DNA sequences from partial 28S regions, the translation elongation factor 1-α gene (tef1α) and RNA polymerase II second largest subunit gene (rpb2) also confirm that B. hainanensis forms an independent lineage within Butyriboletus. Consequently, a description, color photos of fresh basidiomata and line-drawings of microstructures are presented.